2020
DOI: 10.1088/1361-6641/abca0e
|View full text |Cite
|
Sign up to set email alerts
|

Numerical approach to optimizing the doping concentration of the absorber layer to enhance the performance of a CdTe solar cell

Abstract: Cadmium telluride (CdTe)-based solar cells have been proving their potential for high efficiency performance for several decades. However, efficient p-type doping of CdTe has remained a critical challenge for decades thus limiting the performance of this type of solar cell. Thus, this work intends to assess the effects of various dopants and their optimization in order to obtain efficient photovoltaic (PV) performances. In the process we used numerical simulation software SCAPS-1D as it expedites and facilitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…As a result, augmented values of solar cell performance parameters are found [31] However, the performance parameters have a considerably slower acceleration when the layer thickness is over 2.5 μm because that enhances the recombination rate as well [32]. Though performance parameters have not increased at a very commendable rate beyond 1.5 μm, the optimization of absorber thickness is done at 2.5 μm as at lower thickness recombination dominates over the generation of electron-hole pair which can be a negative aspect in terms of device performance experimentally [33].…”
Section: Effect Of Thicknessmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, augmented values of solar cell performance parameters are found [31] However, the performance parameters have a considerably slower acceleration when the layer thickness is over 2.5 μm because that enhances the recombination rate as well [32]. Though performance parameters have not increased at a very commendable rate beyond 1.5 μm, the optimization of absorber thickness is done at 2.5 μm as at lower thickness recombination dominates over the generation of electron-hole pair which can be a negative aspect in terms of device performance experimentally [33].…”
Section: Effect Of Thicknessmentioning
confidence: 99%
“…Again, the diffusion length of the minority carrier along with space charge region (SCR) width is curtailed at a large carrier concentration that stimulates the carrier collection probability within it. As a result, the performance of the device improves [33]. However, the carrier recombination in the bulk increases on account of the high electric field which leads to a drop in short circuit current [31].…”
Section: Effect Of Acceptor Concentrationmentioning
confidence: 99%
“…Since CdTe solar cell is a heterojunction, absorption from other layers within the visible-light range with defect parameters significantly tends to affect the spectral response analysis in the simulation [62]. Moreover, a higher acceptor concentration in the order of 10 16 cm −3 to 10 18 cm −3 tends to limit the space charge region's width, leading to the decrease of photon collection, as well as defects acting as recombination centers [63]. From the simulated EQE, it is also observed that higher acceptor concentration leads to Jsc-JV loss, primarily due to loss of long-wavelength photo-generated carriers.…”
Section: Spectral Response Analysismentioning
confidence: 99%